RADT-07. DETERMINATION OF THE OPTIMAL TIME INTERVAL BETWEEN POST-OPERATIVE MRI AND CT SIMULATION FOR STEREOTACTIC RADIOSURGERY PLANNING. (12th November 2021) - Panse, Drishti; Rogers, Aubrey; Farhangi, Edward; Péris-Celda, Maria; Adil, Khaled
Abstract: BACKGROUND: The incidence of brain metastasis is approximately 200, 000 worldwide annually. Stereotactic radiation therapy of post-operative cavity reduces local recurrence. Surgical cavity size changes significantly with 96.5% demonstrating volumetric change during post-operative period. We sought to define the optimal time interval that preserved the volumetric dimensions between the post-surgical MRI and the CT simulation used for stereotactic radiosurgery planning. METHODS: Seven patients with brain metastasis that underwent surgical resection and stereotactic radiation treatment at Albany Medical Center from February 2019 to April 2020 were included in the study. A total of 8 target lesions were included. Brain lab planning system was used for contouring the target volume. A postoperative MRI within 24-48 hours after surgery was obtained. 3 patients required an additional interim MRI 16-50 days after surgery. The planning CT simulation was performed 2 days prior and up to 15 days after the post-operative/interim MRI and target volumes were compared. RESULTS: The average volume of the post-surgical cavity contoured by the neurosurgeons on the post-operative/interim MRI was 15.96 cc (± 7.79 cc, range of 6.54 -24.9 cc). The average volume of the post-surgical cavity contoured by the radiation oncologists on the planning CT was 15.71 (± 7.49 cc, range of 6.53 -24.31 cc). There was no noticeable change in volume size between post-operative/interim MRI and planning CT up to the period of 15 days. LIMITATION: This was a retrospective pilot study with a small sample size and patients recruited from a single center. CONCLUSION: There is no change in size of the cavity volume for up to 15 days between post-operative/interim MRI and planning CT. This knowledge will help understand the optimal time interval between post-operative MRI and CT simulation for the stereotactic radiation therapy planning.